Implementation of an IoT-Integrated Feedback Control System for Water Quality and Feeding Automation in Aquaculture - Maharmi, Benriwati; Fadli, Ilham; Machdalena, Machdalena; Syabriyana, Maliya; Mirfaturiqa, Mirfaturiqa (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2025)
This study introduces an IoT-based automated system for freshwater aquaculture that enables real-time monitoring of water quality and control of fish feeding. The system utilizes an ESP32 microcontroller integrated with pH, ultrasonic, infrared, temperature, and RTC sensors to monitor pond conditions. A servo motor is used for feed dispensing, while a fluid and clean water pump adjusts pH levels automatically when they fall outside the optimal 6.5–8.5 range. Sensor data is sent to the cloud via the Blynk platform, allowing remote monitoring and notification through a mobile app. Laboratory and field tests over three days demonstrated a fast response time of 1.78 seconds, accurate feed monitoring, and stable pH control. The system offers an efficient, low-cost solution for small to medium-scale aquaculture.